The ATLAS data acquisition and high level trigger system - Onofre, A. (2016)
This paper describes the data acquisition and high level trigger system of the ATLAS experiment at the Large Hadron Collider at CERN, as deployed during Run 1. Data flow as well as control, configuration and monitoring aspects are addressed. An overview of the functionality of the system and of its performance is presented and design choices are discussed.